Systematic analysis on the chemical reaction to the material removal in bonnet polishing of fused silica glass - Xiaolong Ke; Wei Wu; Bo Zhong; Tianyi Wang; Song Yuan; Zhenzhong Wang; Daewook Kim; Jianchun Liu; Min Li; Jiang Guo; Chunjin Wang (Journal of Materials Research and Technology)
Fused silica glass, known for its exceptional physical and chemical properties, is widely used across diverse industries. Cerium oxide (CeO2), a common polishing abrasive, is extensively employed in polishing fused silica surfaces. Studies have revealed that chemical reactions occur on fused silica surfaces during polishing processes with CeO2 abrasives. While these chemical reactions have been studied in the context of chemical-mechanical polishing on fused silica surfaces, the chemical impacts of employing a small, compliant polishing tool on fused silica surfaces remain unclear. In this study, we use CeO2 abrasive and alumina (Al2O3) abrasive as polishing slurries and utilize a bonnet tool to polish fused silica surfaces. Through a comparative analysis of the removal efficiency of the tool influence function, alterations in surface hardness, and the sub-surface damage layer, we found that the primary factor governing material removal is the chemical reactions between CeO2 and fused silica. These reactions effectively soften the fused silica molecule layers and contribute to rapid material removal. This research fills the knowledge gap regarding the chemical effects during bonnet polishing with CeO2 abrasive. It offers valuable insights for efficient material removal control in the context of bonnet polishing fused silica surfaces. These insights will also be applicable to other computer-controlled polishing processes for fused silica glass utilizing CeO2 slurry.